Amine-terminated hyperbranched polyamide covalent functionalized graphene oxide-reinforced epoxy nanocomposites with enhanced toughness and mechanical properties. (July 2019) - Li, Jiongjiong; Zhu, Wenjie; Zhang, Shifeng; Gao, Qiang; Li, Jianzhang; Zhang, Wei
Abstract: Epoxy resins are widely used thermosetting polymers, and they possess many merits including high rigidity, great dimension stability, and good chemical resistance, etc. However, the inherent brittleness limits their broad applications. In this work, amine-terminated hyperbranched polyamide (HBPA-NH2 ) covalent grafted graphene oxide (GO-HBPA) was prepared to improve the fracture toughness of the epoxy polymers. The structures, morphologies, and thermal properties of the GO-HBPA were characterized using FT-IR, XRD, Raman spectroscopy, XPS, SEM, TEM, and TGA. The graphene/epoxy nanocomposites with graphene oxide (GO) or GO-HBPA loadings lower than 0.2 wt% were prepared, and the effects of GO-HBPA on the fracture toughness, mechanical performance, and thermal properties of the GO-HBPA-modified nanocomposites were investigated. The results revealed that the GO-HBPA exhibited great compatibility and dispersion in the epoxy matrix, as well as strong interfacial interactions with the matrix. After the incorporation of GO-HBPA, the fracture toughness, mechanical performances, Tg, and thermal properties of the graphene/epoxy nanocomposites were improved. Especially, the tensile strength, elongation at break, flexural strength, and flexural modulus of the GO-HBPA-0.15% increased by 42.3%, 429%, 41.3%, and 97.3%, respectively, as compared with the neat epoxy. The enhanced performances were attributed to the well dispersed GO-HBPA sheets and the covalent grafted amine-terminated hyperbranched polyamide. Graphical abstract: Image 1 Highlights: Amine-terminated hyperbranched polyamide grafted graphene oxide was prepared. GO-HBPA was used to improve the fracture toughness of the epoxy nanocomposites. GO-HBPA exhibited great dispersion and strong interfacial interactions with the matrix. The nanocomposites exhibited improved fracture toughness, mechanical performances, and Tg . The fracture toughness was attributed to the well dispersed GO-HBPA and the grafted HBPA-NH2 .